Tocilizumab and Active Antibody-Mediated Rejection in Kidney Transplantation: A Literature Review - Cabezas, Lara; Jouve, Thomas; Malvezzi, Paolo; Janbon, Benedicte; Giovannini, Diane; Rostaing, Lionel; Noble, Johan (Frontiers in Immunology, 2022)
Introduction Chronic kidney disease (CKD) is a major public-health problem that increases the risk of end-stage kidney disease (ESKD), cardiovascular diseases, and other complications. Kidney transplantation is a renal-replacement therapy that offers better survival compared to dialysis. Antibody-mediated rejection (ABMR) is a significant complication following kidney transplantation: it contributes to both short- and long-term injury. The standard-of-care (SOC) therapy combines plasmapheresis and Intravenous Immunoglobulins (IVIg) with or without steroids, with or without rituximab: however, despite this combined treatment, ABMR remains the main cause of graft loss. IL-6 is a key cytokine: it regulates inflammation, and the development, maturation, and activation of T cells, B cells, and plasma cells. Tocilizumab (TCZ) is the main humanized monoclonal aimed at IL-6R and appears to be a safe and possible strategy to manage ABMR in sensitized recipients. We conducted a literature review to assess the place of the anti-IL-6R monoclonal antibody TCZ within ABMR protocols. Materials and Methods We systematically reviewed the PubMed literature and reviewed six studies that included 117 patients and collected data on the utilization of TCZ to treat ABMR. Results Most studies report a significant reduction in levels of Donor Specific Antibodies (DSAs) and reduced inflammation and microvascular lesions (as found in biopsies). Stabilization of the renal function was observed. Adverse events were light to moderate, and mortality was not linked with TCZ treatment. The main side effect noted was infection, but infections did not occur more frequently in patients receiving TCZ as compared to those receiving SOC therapy. Conclusion TCZ may be an alternative to SOC for ABMR kidney-transplant patients, either as a first-line treatment or after failure of SOC. Further randomized and controlled studies are needed to support these results.